Low molecular weight heparin treatment of acute moderate and severe pancreatitis: A randomized, controlled,open-label study - Mukaddes Tozlu,; Yusuf Kayar,; Ali Tüzün İnce,; Birol Baysal,; Hakan Şentürk, (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Acute pancreatitis (AP) runs a moderately severe and severe course in 20%-30% of cases. The purpose of the present study was to determine the effect of low molecular weight heparin (LMWH) for the prevention of pancreatic necrosis (PN) in moderately severe and severe AP (MSAP). Materials and Methods: A total of 100 patients with MSAP were randomized to receive either standard care (SC) or SC plus LMWH. LMWH was administered at 1 mg/kg via subcutaneous injection twice a day between days 1 and 7. The revised Atlanta criteria were used in the diagnosis of MSAP. Patients with a Harmless AP Score of ≥1 and a Balthazar computed tomography (CT) score of D and E were included in the study. Results: The mean age±SD of the patients (46 male and 54 female) was 52±19 years (range, 17-100). There were 50 patients in each group. On admission, clinical and laboratory parameters and Balthazar CT scores were similar between the groups. Initially, PN was present in one patient in the LMWH group and two in the SC group. Over the course, PN developed in 3 (6.1%) patients in the LMWH group and 11 (22.9%) in the SC group (p<0.05). Local and systemic complications were significantly lower in the LMWH group (p<0.05). No hemorrhagic complication occurred. Mortality was not significantly different between the groups (p=0.056). Conclusion: Low molecular weight heparin treatment is safe and provides better prognosis in MSAP. Cite this article as: Tozlu M, Kayar Y, İnce AT, Baysal B, Şentürk H. Low molecular weight heparin treatment of acute moderate and severe pancreatitis: A randomized, controlled, open-label study. Turk J Gastroenterol 2019; 30: 81-7.